Synthesis, Characterization, Antibacterial and Urease Inhibition Studies of Some Novel Symmetrical N3,N3'-bis-(disubstituted)isophthalyl-bis-(thioureas) - Jamil, Muhammad; Zubair, Muhammad; Rasool, Nasir; Ali Altaf, Ataf; Rizwan, Komal; Hafeez, Samia; Hussain Bukhari, Iftikhar; Langer, Peter (Asian Journal of Chemistry, 2013)
A series of some novel N3,N3'-bis-(disubstituted)isophthalyl-bis-(thioureas), with general formula [C6H4{CONHCSNR1R2}2], where R1 = H (4a-4d, 4f, 4g, 4i, 4j), C6H5(4e), C6H11(4h) and R2 = C5H4N3(4a), 4-C6H4COOH(4b), 3-NO2C6H4(4c), 2-NO2C6H4(4d), C6H5(4e), 2,4(CH3)2C6H3(4f), C6H11(4g, 4h), C5H4N(4i), 3-NH2C6H4(4j) have been synthesized in good to excellent yields by reaction of isophthaloyl isothiocyanate with primary and secondary amines using dry acetone as solvent. These compounds 3a-j have been characterized by elemental analyses, infrared and 1H NMR spectroscopy. These compounds were screened for their antibacterial activity against bacterial species, Bacillus subtilis, Staphylococcus aureus, Escherichia coli, S. sonii, Salmonella typhi and Pseudomonas aeroginosa. Some compounds showed potent activity against some bacterial strains and others exhibited strong antibacterial activity. The synthesized compounds 4a-j were also evaluated for urease inhibition and found to exhibit varying degree of urease inhibition activity. Compounds 4a-d were found to be the most active, exhibiting IC50 = 26.3 ± 0.5 to 31.1 ± 0.3 μM. It was concluded that these compounds may be a potential source of active antibacterial agents and some of these compounds also exhibit promising urease inhibitory activity.